Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1098/rspb.2007.0237
|View full text |Cite
|
Sign up to set email alerts
|

The cabbage aphid: a walking mustard oil bomb

Abstract: The cabbage aphid, Brevicoryne brassicae, has developed a chemical defence system that exploits and mimics that of its host plants, involving sequestration of the major plant secondary metabolites (glucosinolates). Like its host plants, the aphid produces a myrosinase (b-thioglucoside glucohydrolase) to catalyse the hydrolysis of glucosinolates, yielding biologically active products. Here, we demonstrate that aphid myrosinase expression in head/thoracic muscle starts during embryonic development and protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
183
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(194 citation statements)
references
References 30 publications
7
183
1
3
Order By: Relevance
“…The mechanism by which the beetle controls the hydrolysis of its stored glucosinolates to avoid autointoxication remains to be determined but is likely to be actively controlled. In contrast, the "mustard-oil bomb" in aphids is activated when an individual is attacked by a predator, which benefits the survival of the clonal aphid colony by repelling the predator (17,19,47). Although we cannot rule out the participation of sequestered glucosinolates in a similar defense in Phyllotreta, an additional signaling role is also suggested by previous studies showing that ITCs enhance the response to the male-produced aggregation pheromone (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The mechanism by which the beetle controls the hydrolysis of its stored glucosinolates to avoid autointoxication remains to be determined but is likely to be actively controlled. In contrast, the "mustard-oil bomb" in aphids is activated when an individual is attacked by a predator, which benefits the survival of the clonal aphid colony by repelling the predator (17,19,47). Although we cannot rule out the participation of sequestered glucosinolates in a similar defense in Phyllotreta, an additional signaling role is also suggested by previous studies showing that ITCs enhance the response to the male-produced aggregation pheromone (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 74%
“…sawflies show species-specific sequestration patterns in the hemolymph that were suggested to reflect adaptations to different host plants (16,38). In the crucifer aphid, B. brassicae, glucosinolate accumulation in the hemolymph differs quantitatively between wingless and winged morphs feeding on the same diet, which indicates regulated transport between the gut and hemolymph (17). We also assume that transporters are involved in glucosinolate uptake from the gut in P. striolata.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies have demonstrated that parasitoids are attracted to isothiocyanates (Titayavan and Altieri 1990;Pivnick 1993;Murchie et al 1997;Bradburne and Mithen 2000;Reddy et al 2002;Blande et al 2007). However, parasitoid and predator performance is also known to correlate negatively with glucosinolate content (Harvey et al 2003;Kazana et al 2007;Gols et al 2008). This negative relationship might favor a behavioral response of predators and parasitoids to plant volatiles that contain simple nitriles instead of isothiocyanates.…”
Section: Introductionmentioning
confidence: 99%